A corpus-based computational analysis of philosophical texts: comparing analytic and continental philosophy. (2017) - Botz-Bornstein, Thorsten; Mostafa, Mohamed M.
This is the first modern quantitative study of philosophical texts using corpus linguistics. We compared two sets of texts consisting of ten texts of analytic philosophy and ten texts of continental philosophy by using the Burrows delta consensus tree, principal components analysis, as well as multidimensional scaling (MDS) and cluster analysis. We used a supplementary corpus of ten analytical texts pertaining to film studies. The analysis shows that analytic and continental texts are clearly distinct in stylistic terms though there are divisions within the continental corpus. The results lead to the conclusion that philosophical thought is dependent on language. The introduction of an analytic philosophy of film corpus shows that the focus on a certain topic fractures the linguistic coherence of analytic philosophy. Our focus on two major philosophical schools makes it possible to generalise findings to other philosophical schools.